Language Learning Through Online Collaborative Learning in SMA Negeri 6 Surakarta and SMA Negeri 1 Surakarta: A Qualitative Case Study - Astrini, Atik; Agus Wijayanto; Malikatul Laila (PT. Banjarese Pacific Indonesia, 2024)
Language learning through online collaborative learning is a complex process because it requires thoughtful and pedagogical considerations in its design, implementation, and evaluation. To understand language in online collaborative learning, it is very important to include stakeholders' perspectives on their lived experiences. A qualitative case study was chosen to conduct this research. SMA Negeri 6 Surakarta and SMA Negeri 1 Surakarta were intentionally included in the study. The data were collected from semi-structured interviews of students and teachers and online and offline observations. The collected data were analyzed using the method of constant comparative analysis. The results clarified that several proactive supports (social, pedagogical and technical support) play a crucial role in promoting meaningful collaboration. The presence of the teacher is an important factor that create the collaboration to proceed as desired setting the stage, modeling the desired expectations and guiding the students to achieve the expected results. The assignments and assessments also affect the level of student engagement; therefore, it is recommended to include both formative and summative assessments for both the product and the collaborative process. The findings of this study have implications for the scaffolding and specificity of language learning through online collaboration to support online educators.